Requirement Analysis and Digitalization of Seafood Market Management - Marlindawati, .; Rizqi Dwi, Ramadhan (INTI International University, 2023)
Digitalization is the process of transitioning to a digital business and involves using digital technologies to alter a business model and offer new prospects for income and value creation. The study in this paper was carried out to identify the requirement analysis situated in Karang Agung Ilir Seafood District, Indonesia. The local market sells seafood, including prawns, crabs, and squid. Our findings indicated that the fishermen use conventional markets and rely on the surrounding village area or community market with fluctuating cost control. In this view, we have proposed the digitalization of the traditional market to expand the market locations but reduce costs for example transportation costs, increase efficiency, and avenues for revenue regeneration. Digitalization is the process of moving existing processes into digital technologies using the internet with the purpose of information and knowledge dissemination. Our proposed solution has produced a prototype of Seafood Market Management with functionalities of product data entries, product data ordering, and reports on orders and sales of goods that have been computerized. With the searching technique applied to the application, it speeds up the process of searching for data.